The Relationship Between Pre-existing Coronary Heart Disease and Cognitive Impairment Is Partly Explained by Reduced Left Ventricular Ejection Fraction in the Subjects Without Clinical Heart Failure: A Cross-Sectional Study - Shang, Suhang; Liu, Ziyu; Gao, Jinying; Wang, Jin; Lu, Wenhui; Fei, Yulang; Zhang, Binyan; Mi, Baibing; Li, Pei; Ma, Louyan; Jiang, Yu; Chen, Chen; et al. (Frontiers in Human Neuroscience, 2022)
Background Coronary heart disease (CHD) is closely associated with cognitive impairment, especially in the severe cases of heart failure. However, it is unclear whether cardiac systolic function plays a role in the relationship between pre-existing CHD and cognitive impairment in the subjects without clinical heart failure. Methods 208 subjects from the First Affiliated Hospital of Xi'an Jiaotong University were recruited from June 2014 to January 2015, and were divided into CHD (n=118) and non-CHD (n=90) groups according to the inclusion and exclusion criteria. Global cognitive function of all subjects was assessed by Mini-Mental State Examination (MMSE) and cognitive impairment was defined as the score lower than the cutoff value. Left ventricular ejection fraction (LVEF) was measured using transthoracic echocardiograms. The relationship between pre-existing CHD, LVEF, and cognitive impairment was analyzed by multivariate logistic regression. Results 34 subjects met criteria of cognitive impairment. Univariate analysis showed that the cognitive impairment prevalence in the CHD group was significantly higher than that in the non-CHD group (22.0% vs 8.9%，P=0.011). Multivariate logistic analysis revealed CHD was significantly associated with higher risk of cognitive impairment (OR=3.284 [95% CI, 1.032-10.450], P=0.044) after adjusting for confounds except LVEF. However, OR of CHD decreased (OR=2.127 [95% CI, 0.624-7.254], P=0.228) when LVEF was further corrected as a continuous variable, and LVEF was negatively associated with risk of cognitive impairment (OR=0.928 [95% CI, 0.882-0.976], P=0.004). Conclusions Pre-existing CHD is associated with higher risk of cognitive impairment, and such association can be considerably explained by reduced LVEF. Impaired cardiac systolic function may plays a key role in the relationship between CHD and cognitive impairment among patients with pre-heart failure conditions.